Estimating the environmental impact of diets based on individual-level dietary intake data: infographics on the FAO/WHO GIFT platform - de Quadros, Victoria Padula; Tereza da Silva, Jacqueline; Balcerzak, Agnieszka; Allemand, Pauline; Leclercq, Catherine; Ferrari, Marika; Schmidt Rivera, Ximena; Reynolds, Christian; Holmes, Bridget Anna (Frontiers in Sustainable Food Systems, 2025)
Integrating environmental impacts into dietary assessment is crucial to promote healthy diets from sustainable food systems. Nonetheless, the environmental impacts of individual dietary intake are rarely reported. This paper describes how environmental impacts are integrated into dietary data through the FAO/WHO Global Individual Food Consumption Data Tool (FAO/WHO GIFT). The environmental infographics available on FAO/WHO GIFT offer a user-friendly interface to understand the average footprint of diets, identifying contributing food groups, and exploring variations in environmental impacts. The infographics present estimates for three environmental indicators - greenhouse gas emissions, water use, and land use of dietary intake, allowing users to assess the environmental implications of different diets. Tools to monitor and assess dietary environmental impact, such as those offered by FAO/WHO GIFT, are essential for informing transformation towards healthy diets from sustainable food systems.